CLIMATE CHANGE AND ITS INTERACTION WITH NATURAL, ECONOMIC AND SOCIAL PROCESSES - DRAGOMIR, Robert Gabriel; DRAGOMIR, Lucian Octavian (Annals of Spiru Haret University. Economic Series, 2019)
Human-made GHGs work against us when they trap too much sunlight and block outward radiation. Scientists worry that the accumulation of these gases in the atmosphere has changed and will continue to change the climate. Potential climate risks include more severe weather patterns; hobbled ecosystems, with less biodiversity; changes in patterns of drought and flood, with less potable water; inundation of coastal areas from rising sea levels; and a greater spread of infectious diseases such as malaria, yellow fever, and cholera. On the plus side, climate change might benefit agriculture and forestry in certain locations by increasing productivity as a result of longer growing seasons and increased fertilization. Although climate change is not the same as day-to-day or even year-to-year fluctuations in the weather, the nature of these fluctuations could be altered by climate change.